The Ecological and Anthropogenic Factors Influencing the Nitrification: A review - Ginawi, Amjed; Yunjun, Yan (International Journal of Molecular Microbiology, 2018)
This review focuses on the influence of the environmental factors and the human impact on the nitrification, specifically aerobic ammonia oxidation that is the degree limiting stage of nitrification and is mediated by ammonia oxidizing archaeal and bacteria (AOA/AOB). The understanding the primary drivers of ammonia oxidizing distribution and abundance in sediments are increasing interest around the globe. Many studies evaluated the environmental sediment of the communities’ ammonia oxidizing, but a few issues are known about sediments ammonia oxidizing. The sediment characteristics that have significant control in determining ammonia-oxidizing communities include ammonia substrates, pH, temperature, carbon, and oxygen, these environmental parameters represented reasons the AOA higher than the AOB in various sediments and numerous ecological, as they can inhabit possibility specialized that are unavailable to the AOB.